Effect of sevoflurane, propofol and propofol with dexmedetomidine as maintenance agent on intracranial pressure in the Trendelenburg position during laparoscopic surgeries - Manoj Kamal; Sanjeev Kumar Chawriya; Mritunjay Kumar; Narendra Kaloria; Ankur Sharma; Pradeep Bhatia; Geeta Singariya; Bharat Paliwal (Wolters Kluwer Medknow Publications, 2023)
Background and Aim: Pneumoperitoneum (PP) and the Trendelenburg position (TP) in laparoscopic surgeries are associated with rise in intracranial pressure (ICP). The optic nerve sheath diameter (ONSD) is a surrogate marker of ICP. The study aimed to evaluate the effect of sevoflurane, propofol and propofol with dexmedetomidine as maintenance agent on ICP in TP during laparoscopic surgeries. Material and Methods: A total of 120 American Society of Anesthesiologists (ASA) physical status I/II patients, aged 18-65 years were randomly allocated into three groups: sevoflurane as group S, propofol as group P, and propofol with dexmedetomidine as group PD. The intra-abdominal pressure (IAP) was kept in the range of 12-14 mmHg and TP varied between 15°- 45° angle. The primary objective was comparison of ICP and secondary objectives were IOP, intraoperative hemodynamic and postoperative recovery characteristics among groups. The ONSD and IOP were measured in both eyes 10 min after endotracheal intubation (T0), 5 min after CO2 insufflation (T1), 5 min after TP (T2) and 5 min after deflation of gas (T3). The data were analyzed by using the Statistical Package for Social Sciences version 23. Results: ONSD and IOP at T1 and T2 were significantly higher than T0 in all groups, but no significant difference was found among the intergroup groups. Significantly lower heart rate and mean blood pressure were observed in PD group at T1 and T2 compared to group S and group P. Conclusion: The rise in ICP was comparable among sevoflurane, propofol, and propofol-dexmedetomidine combination as a maintenance agent during laparoscopic surgeries in TP.